Blending Common Core Standards and Functional Skills in Thematic Units for Students with Significant Intellectual Disabilities - Cooper-Duffy, Karena; Hyer, Glenda (Journal of the American Academy of Special Education Professionals, 2014)
Many teachers who educate students with significant intellectual disabilities struggle with the requirements for teaching academics linked to the Extended Common Core State Standards (ECCSS, 2010) while also balancing the need to teach functional skills. This article provides a practical way of creating thematic units that focuses on functional skill topics to teach both academics linked to the ECCSS (2010) and functional skills in small groups. A detailed description on how to collaborate with all stakeholders to create a thematic unit about a functional skill topic to teach both academics and functional skills are provided. The article also includes examples of: (a) a lesson plan, (b) vocabulary words, (c) task analysis of a functional skill, (c) systematic instruction plan, and (d) data collection sheets.